PENGARUH LITERASI EKONOMI DAN TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI YANG DIMEDIASI OLEH KONTROL DIRI - Lilis Farida; Riza Yonisa Kurniawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractHigh school students are included in the category of teenagers, they are still not able to control themselves optimally because they are in the stage of searching for identity. This can trigger irrational consumption behavior. It’s needed to have economic literacy and a good peer environment as well as positive self-control so that students can behave rationally. In this study using quantitative methods. The purpose of this research was to knowing the effect of economic literacy and peers on consumption behavior through self-control. This study uses a simple random sampling technique in determining the sample. This research was conducted at SMA Negeri 1 Taman. The research sample was 11th grade social studies students, totalling 102 respondents. The results of the study are (1) existence an insignificant and positive impact between economic literacy on self-control. (2) existence a significant and positive impact economic literacy on consumption behavior. (3) existence a significant and negative impact between peers on self-control. (4) existence is a positive and significant impact between peers on consumption behavior. (5) existence a positive and significant impact  self-control on consumption behavior. (6) existence an insignificant and positive effect of self-control as a intervening variable of the effect of economic literacy on consumption behavior. (7) existence an insignificant and negative effect of self-control as a intervening  variable of peer influence on consumption behavior.Keywords: Economic literacy, peers, self control, consumption behavior.AbstractHigh school students are included in the category of teenagers, they are still not able to control themselves optimally because they are in the stage of searching for identity. This can trigger irrational consumption behavior. It’s needed to have economic literacy and a good peer environment as well as positive self-control so that students can behave rationally. In this study using quantitative methods. The purpose of this research was to knowing the effect of economic literacy and peers on consumption behavior through self-control. This study uses a simple random sampling technique in determining the sample. This research was conducted at SMA Negeri 1 Taman. The research sample was 11th grade social studies students, totalling 102 respondents. The results of the study are (1) existence an insignificant and positive impact between economic literacy on self-control. (2) existence a significant and positive impact economic literacy on consumption behavior. (3) existence a significant and negative impact between peers on self-control. (4) existence is a positive and significant impact between peers on consumption behavior. (5) existence a positive and significant impact  self-control on consumption behavior. (6) existence an insignificant and positive effect of self-control as a intervening variable of the effect of economic literacy on consumption behavior. (7) existence an insignificant and negative effect of self-control as a intervening  variable of peer influence on consumption behavior.Keywords: Economic literacy, peers, self control, consumption behavior.